Heart rate patterns of captive Asian elephant (Elephas maximus) in their natural habitat at Wild Elephant Valley, Xishuangbanna of China - Fangyi Zhou; Mingwei Bao; Xianming Guo; Qingzhong Shen; Jiming Chen; Duo Li; Hong Bao; Li Zhang (Heliyon, 2024)
There are few studies on the changes of heart rate of the Asian elephant (Elephas maximus), one of the largest tropical terrestrial mammals, with its self-factors and external environment. By measuring the heart rate of 35 Asian elephants, ranging in age from 4 months to 52 years, using a non-invasive electrocardiogram sensor in their natural habitat at Wild Elephant Valley, Xishuangbanna of China, we found factors that significantly influenced the HR were season, phase of the day, age, body weight, and the interaction between some of the above factors. We also observed that Asian elephants had lower resting heart rate in the morning of hot season than the cold and mild season, and the differences were significant, but the heart rate increased to similar levels in the afternoon regardless of the season. HR also decreased with age in all seasons and phases of the day. However, there was no significant effect of sex. This study reveals the adaptability of Asian elephant to tropical environment, and provides a basic reference for heart rate of Asian elephant under various natural conditions.